Correlation Between Cutting Force and Residual Stress in Dry End-Milling of Inconel HX - N. A., Mohd Nor; B. T. H. T., Baharudin; Z., Leman; M. K. A., Mohd Ariffin (International Journal of Integrated Engineering, 2022)
Residual stress in the end-milled subsurface can significantly affect the fatigue performance of end-milled material. In the end-milling process, the generation of residual stress is extremely complex, which is closely related to the spindle speed, feed per tooth and cutting force. Thus, it is crucial to elucidate the influence of spindle speed and feed per tooth on cutting force and residual stress, also the correlation between cutting force and residual stress in terms of spindle speed and feed per tooth. According to this, dry end-milling of Inconel HX was performed by climb-milling using Kennametal KYS40 solid ceramic end-mill. From this experimental test, cutting force and residual stress showed a U-shaped relationship with the increase of spindle speed, while cutting force and residual stress showed a linear relationship with the increase of feed per tooth. Furthermore, for low cutting force and residual stress, the focus should be on choosing the optimum combination of spindle speed (21,400 to 24,100 rpm) and feed per tooth (0.014 to 0.016 mm/tooth).